Kajian Penerapan Pendekatan Arsitektur Regionalisme pada Museum Batik Surakarta - Anisa Desita Widodo; Dyan Agustin (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
Batik museum is a place to preserve batik as part of the Indonesian local culture in the future. Currently, several batik-producing cities have their own batik museums, one of which is the Surakarta Batik Museum. The building uses a regionalism architectural design approach that is relevant to its function, namely elevating the local culture of Surakarta. The successness in applying the regionalism architectural approach can be seen in the implementation of building elements. This study aims to examine the successful application of the regionalism architectural approach to the Surakarta Batik Museum which is based on three regionalism architectural factors. The research uses qualitative methods with the acquisition of primary data and secondary data. The results of this study explain the success in applying the regionalism architectural approach to the Surakarta Batik Museum.